Catalytic cracking catalyst resistant to nickel and vanadium pollution and preparation method thereof

By using boron-phosphoraluminum rare earth composition in catalytic cracking catalyst, the problem of the catalyst being contaminated by nickel and vanadium when treating heavy raw oil is solved, and the activity stability and anti-pollution effect of the catalyst are achieved.

CN119869606AActive Publication Date: 2025-04-25PETROCHINA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202311377756.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-23
Publication Date
2025-04-25
Estimated Expiration
2043-10-23

AI Technical Summary

Technical Problem

When treating heavy raw oil, catalytic cracking catalysts are susceptible to contamination by metals such as nickel and vanadium, resulting in a decrease in catalyst activity and unstable process operation.

Method used

The boron-phosphorus aluminum rare earth composition is used as the additive component and added to the catalytic cracking catalyst. The mesoporous structure is formed by calcination to fix the boron element. The rare earth element is used to capture vanadium metal, and AlPO4 inhibits the dealumination of the molecular sieve.

Benefits of technology

Effectively inhibit the pollution of nickel and vanadium, improve the activity stability of the catalyst, reduce the destruction effect of heavy metals on molecular sieves, and extend the service life of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004509373600000061
    Figure BDA0004509373600000061
  • Figure BDA0004509373600000071
    Figure BDA0004509373600000071
  • Figure BDA0004509373600000091
    Figure BDA0004509373600000091
Patent Text Reader

Abstract

The invention discloses a nickel and vanadium pollution resistant catalytic cracking catalyst and a preparation method thereof. The preparation method comprises the following steps: mixing a first raw material with water, pulping, and then carrying out spray molding, roasting, washing and drying to obtain the catalytic cracking catalyst, the first raw material comprises a boron-phosphorus-aluminum rare earth composition, a molecular sieve, clay and a binder; the boron-phosphorus-aluminum-rare earth composition is a mixture of AlPO4, B, P, Al and rare earth and is subjected to roasting treatment in the preparation process. The element B can effectively inhibit nickel pollution, the rare earth element can effectively capture the element V, and AlPO4 can effectively inhibit dealumination of the molecular sieve and counteract toxic effects of B, V and the like on the catalyst; and in the preparation process of the boron-phosphorus-aluminum rare earth composition, a mesoporous structure is formed through roasting, and boron is fixed in a pore channel, so that in the preparation process of the catalyst, the possibility of migrating to the surface of the molecular sieve to damage the skeleton structure of the molecular sieve is low, and the catalyst can maintain relatively high activity stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic cracking catalysts, and in particular to a catalytic cracking catalyst resistant to nickel and vanadium pollution and a preparation method thereof. Background Art

[0002] In recent years, with the increasing depletion of oil resources, for economic reasons, many refineries' catalytic cracking units have begun to process inferior and heavy raw materials. These heavy crude oils often contain metals such as nickel, vanadium, iron, sodium, and calcium. These metals often deposit on the catalytic cracking catalyst, causing irreparable damage to the catalyst, thereby affecting the operation of the entire catalytic cracking process.

[0003] Among these metals, nickel, vanadium and iron have the greatest impact on the catalyst. Vanadium will form vanadic acid under the action of high-temperature water vapor, which will cause the molecular sieve in the catalyst to dealuminate and the catalyst activity to decrease. The toxicity of nickel is manifested in a strong catalytic dehydrogenation effect, which makes the selectivity of the catalytic cracking reaction worse and increases the yield of hydrogen and catalytic coke (coke generated by the catalytic cracking reaction on the acid center). At the same time, the presence of nickel will also aggravate the destructive effect of vanadium on the molecular sieve. The presence of iron metal is mainly manifested in the formation of a eutectic body with low-melting point components, forming iron nodules on the catalyst surface, and blocking the pores of the catalyst.

[0004] In order to reduce the poisoning effect of such metals on the catalyst, the most common method is to add a passivator to the catalytic cracking unit. The passivator is mainly a compound of antimony, bismuth, tin, rare earth, boron, etc., which is dispersed in a solvent and added to the crude oil. In the reactor, these metal compounds can react with nickel and vanadium to form relatively stable compounds, reducing the poisoning effect of nickel and vanadium on the catalyst. However, the toxicity of antimony-based, bismuth-based and tin-based nickel passivators is relatively strong, causing great pollution to the environment, thus limiting their application.

[0005] The preparation technology of catalytic cracking catalysts resistant to heavy metal pollution is to adjust the physical and chemical properties of the catalytic cracking catalyst matrix, such as specific surface area, pore volume and chemical composition, through different modification methods. Since heavy metals are first deposited on the catalyst matrix surface during the catalytic cracking process, the heavy metals are captured on the matrix surface in time to protect the active components of the molecular sieve. At present, different preparation technologies of catalytic cracking catalysts resistant to heavy metal pollution have been developed successively, and have become a hot spot in the field of catalytic cracking research. Summary of the invention

[0006] The object of the present invention is to provide a catalytic cracking catalyst resistant to nickel and vanadium pollution and a preparation method thereof.

[0007] The present invention prepares a boron-phosphorus-aluminum rare earth composition, and adds the composition as an additive component into a catalytic cracking catalyst to prepare a catalytic cracking catalyst resistant to nickel and vanadium metal pollution. The composition is a mixture of AlPO4, B, P, Al and rare earth. The presence of the B element can effectively inhibit the pollution of nickel metal; the presence of the rare earth element can effectively capture the V element, fix V in the composition, and it is not easy to migrate to the molecular sieve component, thus greatly reducing the destructive effect of V on the molecular sieve; AlPO4 can effectively inhibit the dealumination of the molecular sieve and offset the poisoning effect of B, V and the like on the catalyst.

[0008] In order to achieve the above purpose, the present invention adopts the following technical solutions:

[0009] The first aspect of the present invention provides a method for preparing a catalytic cracking catalyst resistant to nickel and vanadium pollution, comprising the following steps:

[0010] The first raw material is mixed with water, slurried, and then spray-formed, roasted, washed, and dried to obtain the catalytic cracking catalyst; the first raw material includes a boron-phosphorus-aluminum rare earth composition, a molecular sieve, clay, and a binder;

[0011] The boron-phosphorus-aluminum-rare earth composite is a mixture of AlPO4 and B, P, Al and rare earth, and is calcined during the preparation process.

[0012] According to the preparation method of the present invention, preferably, the first raw material further includes pseudo-boehmite.

[0013] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum-rare earth composition is prepared by reacting an aluminum compound, phosphoric acid, a boron compound, a rare earth compound and a dispersant and calcining at 400-700°C;

[0014] The boron compound is added according to the boron content of the total mass of the boron-phosphorus-aluminum rare earth composition of 2wt% to 6wt%, more preferably 2wt% to 4wt%;

[0015] The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):1, more preferably (0.9-1.5):1;

[0016] The rare earth compound is added according to the rare earth element content of the total mass of the boron-phosphorus-aluminum rare earth composition of 1.5wt% to 25wt%;

[0017] The dispersant is added at 3wt% to 15wt% of the total mass of the boron-phosphorus-aluminum rare earth composition.

[0018] According to the preparation method of the present invention, preferably, the boron-phosphorus-aluminum rare earth composition is prepared by the following method 1 or method 2:

[0019] Method 1: Add an aluminum compound to water, then drop phosphoric acid; then add a boron compound, a rare earth compound and a dispersant, and stir to obtain a sol containing boron, phosphorus, aluminum and rare earth;

[0020] Drying the sol containing boron, phosphorus, aluminum and rare earth, and calcining at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum-rare earth composite;

[0021] Method 2: Mix and disperse the aluminum compound in water, then drop phosphoric acid, add a rare earth compound and a dispersant to obtain a sol containing phosphorus, aluminum and rare earth; dry the sol containing phosphorus, aluminum and rare earth to obtain an intermediate product;

[0022] The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum rare earth composite.

[0023] In the preparation process of the boron-phosphorus-aluminum rare earth composition of the present invention, a mesoporous structure is formed through calcination, and boron is fixed in the pores of the composition. During the preparation process of the catalyst, it is not easy to migrate to the surface of the molecular sieve to destroy the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability; the rare earth in the composition can effectively capture vanadium metal, so that vanadium is fixed in the phosphorus and aluminum structure, and the probability of its contact with the molecular sieve is greatly reduced, thereby achieving a better anti-vanadium effect.

[0024] In method 1 and method 2, the calcination temperature is preferably 400-700°C, and the time is preferably 1-4 hours. In addition, the drying temperature is 80-120°C, and the time is 5-24 hours. In the preparation process of the boron-phosphorus-aluminum rare earth composition of the present invention, in method 1 and method 2, after the phosphoric acid is added dropwise, aging can be carried out under stirring for a period of time, for example, 1-5 hours. In method 1, it is preferred to continue stirring for 0.5-3 hours after adding the boron compound.

[0025] In the process of preparing the boron-phosphorus-aluminum rare earth composition, preferably, the aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride. More preferably, the aluminum compound is aluminum nitrate or pseudo-boehmite.

[0026] In the process of preparing the boron-phosphorus-aluminum rare earth composition, preferably, the concentration of the phosphoric acid is 20wt% to 85wt%, preferably 30wt% to 70wt%.

[0027] In the process of preparing the boron-phosphorus-aluminum rare earth composition, preferably, the boron compound is a soluble boron compound selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate. More preferably, the boron compound is boric acid or boric anhydride.

[0028] In the process of preparing the boron-phosphorus-aluminum rare earth composition, preferably, the rare earth compound is a compound of lanthanum or cerium, more preferably a nitrate, chloride, oxide or carbonate of lanthanum or cerium, and further preferably a nitrate or carbonate of cerium.

[0029] In the process of preparing the boron-phosphorus-aluminum-rare earth composition, preferably, the dispersant is one or a combination of two or more of citric acid, tartaric acid, C2-8 alcohol, polyethylene glycol, cellulose derivatives, polyacrylamide and its derivatives, and guar gum.

[0030] More preferably, the cellulose derivative is sodium hydroxymethylcellulose, methyl hydroxyethyl cellulose or hydroxypropyl methylcellulose.

[0031] More preferably, the C2-8 alcohol is ethanol, ethylene glycol, glycerol, isopropanol, n-propanol or 1,3-butanediol.

[0032] In the catalytic cracking catalyst preparation process, preferably, the specific preparation process of the catalytic cracking catalyst includes:

[0033] Adding the second raw material into water and mixing evenly, adding a binder after aging to form a catalyst matrix slurry; the second raw material is part of the components in the first raw material, including the boron phosphate aluminum rare earth composition and clay, or the second raw material includes the boron phosphate aluminum rare earth composition, clay and pseudo-boehmite;

[0034] The molecular sieve is added into water, sheared, and then added into the catalyst matrix slurry, slurried, spray-formed, calcined, washed, and dried to obtain the catalytic cracking catalyst.

[0035] More preferably, the aging temperature is 40 to 90° C., further preferably 75° C., and the aging time is 1 to 5 hours, further preferably 1 hour.

[0036] In the preparation process of the catalytic cracking catalyst, when the first raw material is mixed with water for slurrying, the solid content of the system is preferably 10wt% to 45wt%. The calcination temperature of the catalytic cracking catalyst is preferably 400 to 800°C, and the time is preferably 0.5 to 3h. More preferably, calcination is performed at 500°C for 1 hour. The drying temperature is preferably 80 to 150°C, and the time is preferably 5 to 24h. The washing is performed by water washing.

[0037] In the preparation process of the catalytic cracking catalyst, preferably, the corresponding raw materials of each component in the obtained catalytic cracking catalyst, calculated on a dry basis of oxides, have a molecular sieve content of 36wt% to 50wt%, a borophosphorus-aluminum rare earth composition content of 5wt% to 25wt%, a clay content of 21wt% to 43wt%, a pseudo-boehmite content of 0 to 13wt%, and a binder content of 8wt% to 15wt%.

[0038] In the process of preparing the catalytic cracking catalyst, preferably, the molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve and ZSM-5 molecular sieve.

[0039] In the process of preparing the catalytic cracking catalyst, preferably, the clay is selected from one or a combination of two or more of kaolinite, montmorillonite and attapulgite.

[0040] In the process of preparing the catalytic cracking catalyst, preferably, the binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

[0041] The second aspect of the present invention provides a catalytic cracking catalyst resistant to nickel and vanadium pollution, which is prepared by the preparation method provided in the first aspect above.

[0042] The components of the catalytic cracking catalyst resistant to nickel and vanadium pollution correspond to raw materials, and the content of the molecular sieve is 36wt% to 50wt% calculated on a dry oxide basis.

[0043] According to the catalytic cracking catalyst resistant to nickel and vanadium pollution of the present invention, preferably, the corresponding raw materials of each component in the catalytic cracking catalyst resistant to nickel and vanadium pollution, calculated on a dry basis of oxides, have a content of the boron phosphorus aluminum rare earth composition of 5wt% to 25wt%.

[0044] According to the catalytic cracking catalyst resistant to nickel and vanadium pollution of the present invention, preferably, the content of the clay in the raw materials corresponding to the components in the catalytic cracking catalyst resistant to nickel and vanadium pollution is 21wt% to 43wt% based on dry oxides.

[0045] According to the catalytic cracking catalyst resistant to nickel and vanadium pollution of the present invention, preferably, the components of the catalytic cracking catalyst resistant to nickel and vanadium pollution correspond to raw materials, and the content of the pseudo-boehmite is 0-13wt%, preferably 5-13wt%, calculated on a dry basis of oxides.

[0046] According to the catalytic cracking catalyst resistant to nickel and vanadium pollution of the present invention, preferably, the content of the binder in the components corresponding to the raw materials in the catalytic cracking catalyst resistant to nickel and vanadium pollution is 8wt% to 15wt% on a dry basis of oxides.

[0047] The present invention adds a boron-phosphorus-aluminum-rare earth composition as an additive component into the catalyst preparation to obtain a catalytic cracking catalyst resistant to nickel and vanadium pollution. The composition is a mixture of AlPO4, B, P, Al and rare earth. The presence of the B element can effectively inhibit the pollution of nickel metal; the presence of the rare earth element can effectively capture the V element, fix V in the composition, and it is not easy to migrate to the molecular sieve component, thus greatly reducing the destructive effect of V on the molecular sieve; the presence of AlPO4 can effectively inhibit the dealumination of the molecular sieve and offset the poisoning effect of B, V and the like on the catalyst.

[0048] During the preparation of the boron-phosphorus-aluminum rare earth composite, boron is fixed in the pores of the composite through calcination to form a mesoporous structure. During the preparation of the catalyst, it is not easy to migrate to the surface of the molecular sieve and destroy the skeleton structure of the molecular sieve, so that the catalyst can maintain a relatively high activity stability. DETAILED DESCRIPTION

[0049] In order to explain the present invention more clearly, the present invention is further described below in conjunction with preferred embodiments. It should be understood by those skilled in the art that the following specific description is illustrative rather than restrictive, and should not be used to limit the scope of protection of the present invention.

[0050] All numerical specifications herein (e.g., temperature, time, concentration, and weight, etc., including ranges for each thereof) are generally approximate values ​​that may be appropriately varied (+) or (-) in increments of 0.1 or 1.0. All numerical specifications may be understood as being preceded by the term "about."

[0051] The raw materials and properties used in the following examples are:

[0052] Kaolin, silica sol (solid content 40wt%), aluminum sol (solid content 18wt%), various molecular sieves, pseudo-boehmite (dry basis is the part after ignition loss, its molecular weight is 101.96) and hydrochloric acid (concentration 30wt%) are all industrial grade; nickel nitrate, boric acid, boric anhydride, aluminum nitrate, aluminum chloride, ammonium metavanadate, oxalic acid, cerium nitrate, cerium carbonate, lanthanum oxide, glycerol, ethylene glycol, isopropanol, n-propanol, 1,3-butanediol, methyl hydroxyethyl cellulose, hydroxypropyl methyl cellulose, sodium hydroxymethyl cellulose, analytical grade. Phosphoric acid 85wt%.

[0053] Catalyst micro-reaction activity evaluation method: The micro-reaction activity evaluation device developed by Beijing Huier Sanji Green Chemical Technology Co., Ltd. was used for evaluation. The raw oil used was 3 million tons / year of catalyst from Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800°C and 100% steam for 17 hours before evaluation.

[0054] Catalyst reaction performance evaluation method:

[0055] The catalyst was contaminated with heavy metals before evaluation. The method of heavy metal contamination simulated the content of nickel and V in industry: an aqueous solution of nickel nitrate, ammonium metavanadate, and oxalic acid (10000ppm Ni, 5000ppm V based on the dry basis of the catalyst) was impregnated into the catalyst, dried at 120°C, and calcined at 550°C for 4 hours. The reaction performance was evaluated using an ACE device. The raw oil used was 3 million tons / year of catalytic material from Lanzhou Petrochemical Company. The properties of the raw oil are shown in Table 1. The catalyst was aged at 800°C and 100% steam for 8 hours before evaluation.

[0056] Table 1 Raw oil properties

[0057]

[0058]

[0059] Preparation of boron phosphorus aluminum rare earth composite:

[0060] Composition 1

[0061] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 3 L of water under stirring until dissolved, 1152.94 g of 85 wt% phosphoric acid (P: 10 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 186 g of boric acid (B: 3 mol), 386 g of cerium nitrate, and 15.27 g of propylene glycol were added, and stirring was continued for 0.5 h. The sol was dried in an oven at 100 ° C for 24 h and calcined at 600 ° C for 1 h to obtain composition 1.

[0062] Composition 2

[0063] 1019.60g of dry pseudo-boehmite (Al: 10mol) was dispersed in 3L of water under stirring, and stirring was continued for 0.5h. 700.00g of 70wt% phosphoric acid (P: 5mol) was added dropwise under stirring to form a homogeneous sol. Stirring was continued for 1h. Then 222.78g of boric anhydride (B: 6.4mol), 102.2g of cerium carbonate, 42.7g of methyl hydroxyethyl cellulose and 43.2g of ethylene glycol were added. Stirring was continued for 1h. The sol was dried in an oven at 80°C for 20h and calcined at 500°C for 2h to obtain composition 2.

[0064] Composition 3

[0065] 1333.40 g of aluminum chloride (Al: 10 mol) was dissolved in 1 L of water under stirring, and 6533.33 g of 30 wt% phosphoric acid (P: 20 mol) was added dropwise under stirring to form a homogeneous sol. The mixture was stirred for 2 h, and then 742.07 g of ammonium borate trihydrate (B: 13 mol), 22.94 g of cerium oxide, 20.00 g of sodium hydroxymethyl cellulose and 16.15 g of isopropanol were added. The mixture was stirred for 1 h. The sol was dried in an oven at 120 ° C for 6 h and calcined at 450 ° C for 3 h to obtain composition 3.

[0066] Composition 4

[0067] 2129.96 g of aluminum nitrate (Al: 10 mol) was added to 2 L of water under stirring until dissolved, 1633.33 g of 40 wt% phosphoric acid (P: 6.7 mol) was added dropwise to the dissolved aluminum nitrate to form a homogeneous sol, and then 281.05 g of ammonium fluoroborate (B: 2.7 mol), 511.71 g of lanthanum chloride, 100 g of n-propanol and 32.5 g of hydroxypropyl methylcellulose were added, and stirring was continued for 0.5 h. The sol was dried in an oven at 150 ° C for 7 h and calcined at 400 ° C for 4 h to obtain composition 4.

[0068] Composition 5

[0069] 1333.40g aluminum chloride (Al: 10mol) was dissolved in 1L water under stirring, 6533.33g 30wt% phosphoric acid (P: 20mol) was added dropwise under stirring, and stirring and aging was continued for 3h. 458.55g lanthanum nitrate and 361.94g 1,3-butanediol were added to form a sol, and the sol was dried in an oven at 130°C for 16h and ground into powder.

[0070] 354 g of boric acid (B: 5.7 mol) was dissolved in 500 mL of water, added to the above powder and immersed for 1 h, dried at 120° C. for 5 h, and calcined at 450° C. for 3 h to obtain composition 5.

[0071] Comparative composition 1

[0072] 1019.60 g of dry pseudo-boehmite (Al: 10 mol) was dispersed in 2.5 L of water under stirring, and stirring was continued for 0.5 h. 700.00 g of 70 wt% phosphoric acid (P: 10 mol) was added dropwise under stirring, and stirring and aging was continued for 1 h. Then 222.78 g of boric anhydride (B: 6.4 mol) was added and stirred for 1 h. 102.2 g of cerium carbonate, 45.7 g of methyl hydroxyethyl cellulose and 42.0 g of ethylene glycol were added and stirring was continued for 1 h. The sol was dried in an oven at 110 ° C for 10 h to obtain a comparative composition 1.

[0073] Comparative composition 2

[0074] 1019.60 g of dry pseudo-boehmite was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. 700.00 g of 70 wt% phosphoric acid was added dropwise under stirring and the stirring was continued for 1 h. Then 208.86 g of boric anhydride was added and the stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 8 h and calcined at 500 ° C for 2 h to obtain comparative composition 2.

[0075] Comparative composition 3

[0076] 1019.60 g of dry pseudo-boehmite was dispersed in 3 L of water under stirring and the stirring was continued for 0.5 h. Then 151.89 g of boric anhydride was added and stirred for 1 h. 73.00 g of cerium carbonate, 18.0 g of methyl hydroxyethyl cellulose and 42.0 g of ethylene glycol were added and the stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 8 h and calcined at 500 ° C for 2 h to obtain comparative composition 3.

[0077] Comparative composition 4

[0078] 1019.60 g of dry pseudo-boehmite was dispersed in 3 L of water under stirring, and stirring was continued for 0.5 h. 700.00 g of 70 wt% phosphoric acid was added dropwise under stirring, and stirring and aging were continued for 1 h. 87.45 g of cerium carbonate, 29.75 g of methyl hydroxyethyl cellulose and 42.0 g of ethylene glycol were added, and stirring was continued for 1 h. The sol was dried in an oven at 120 ° C for 8 h and calcined at 500 ° C for 2 h to obtain comparative composition 4.

[0079] The compositions and some preparation conditions of the above-obtained compositions 1-5 and comparative compositions 1-4 are shown in Table 2.

[0080] Table 2 Compositions and preparation conditions of compositions 1-5 and comparative compositions 1-4

[0081]

[0082] Example 1

[0083] This example uses composition 1 to prepare catalytic cracking catalyst S1, comprising the following steps:

[0084] In a reactor with water bath heating, 2.5L of water, 870g of kaolin, and 150g of pseudo-boehmite were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol and 600g of composition 1 were added and stirred continuously to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the obtained microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 150°C for 5 hours to obtain catalyst S1.

[0085] Example 2

[0086] This example uses composition 2 to prepare catalytic cracking catalyst S2, comprising the following steps:

[0087] In a reactor with water bath heating, add 2L of water and 840g of attapulgite, mix well, stir for 1 hour, age at 75°C for 1h, then add 1833g of aluminum sol and 750g of composition 2 and continue stirring to form a catalyst matrix slurry; add 1.7L of water to a slurrying tank, add 980g of RDSY+100g of REY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, slurry for 1h, and then spray mold, calcine the obtained microspheres at 500°C for 1 hour, wash with water, and dry at 110°C for 12h to obtain catalyst S2.

[0088] Example 3

[0089] This example uses composition 3 to prepare catalytic cracking catalyst S3, comprising the following steps:

[0090] In a reactor with water bath heating, 3.5L water, 1140g montmorillonite and 390g pseudo-boehmite were added and mixed evenly, 190g hydrochloric acid was added dropwise, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1333g aluminum sol and 150g composition 3 were added and continued to be stirred to form a catalyst matrix slurry; 4L water was added to a pulping tank, and 980g RDSY+100g REY molecular sieves were added, and after passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry, and after pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 5 hours to obtain catalyst S3.

[0091] Example 4

[0092] This embodiment uses composition 4 to prepare catalytic cracking catalyst S4, comprising the following steps:

[0093] In a reactor with water bath heating, 2.5L of water, 1140g of halloysite, and 180g of pseudo-boehmite were added and mixed evenly, 90g of hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 1333g of aluminum sol and 300g of composition 4 were added and continued to stir to form a catalyst matrix slurry; 3.5L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 100°C for 24 hours to obtain catalyst S4.

[0094] Example 5

[0095] This embodiment uses composition 5 to prepare catalytic cracking catalyst S5, comprising the following steps:

[0096] In a reactor with water bath heating, 3.5L of water, 840g of kaolin and 240g of pseudo-boehmite were added and mixed evenly, 120g of hydrochloric acid was added dropwise, and after stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1125g of silica sol and 450g of composition 5 were added and continued to stir to form a catalyst matrix slurry; 3.0L of water was added to a pulping tank, and 600g of β molecular sieve was added, which was passed through a high-speed shearing machine for 20 minutes and then added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 80°C for 24 hours to obtain catalyst S5.

[0097] Example 6

[0098] This example uses composition 2 to prepare catalytic cracking catalyst S6, comprising the following steps:

[0099] In a reactor with water bath heating, 4L of water, 1050g of kaolin and 270g of pseudo-boehmite were added and mixed evenly, 130g of hydrochloric acid was added dropwise, and after stirring for 1 hour, it was aged at 75°C for 1 hour, and then 900g of silica sol and 4240g of composition 2 were added and continued to stir to form a catalyst matrix slurry; 4L of water was added to a pulping tank, and 900g of RDSY + 600g of ZSM-5 molecular sieve were added. After passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry. After pulping for 1 hour, it was spray-formed, and the obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 6 hours to obtain catalyst S6.

[0100] Comparative Example 1

[0101] This comparative example prepares catalytic cracking catalyst D1, in which no boron-phosphorus-aluminum rare earth composition is used, comprising the following steps:

[0102] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1 hour, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a beating tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20 minutes, add to the catalyst matrix slurry, beating for 1 hour, and then spray forming. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried at 100°C for 16 hours to obtain catalyst D1.

[0103] Comparative Example 2

[0104] This comparative example prepares catalytic cracking catalyst D2, wherein boric acid is used instead of the boron-phosphorus-aluminum rare earth composition, comprising the following steps:

[0105] In a reactor with water bath heating, add 2.5L water, 1470g kaolin, 150g pseudo-boehmite, 422g boric acid, then slowly add 90g hydrochloric acid and mix evenly. After stirring for 1 hour, age at 75°C for 1h, and then add 1666g aluminum sol to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold. The obtained microspheres are calcined at 500°C for 1 hour, washed with water, and dried at 110°C for 10h to obtain catalyst D2.

[0106] Comparative Example 3

[0107] This comparative example prepares catalytic cracking catalyst D3, wherein a rare earth compound (rare earth accounts for 1wt% of the dry basis content) and a dispersant are used instead of the boron-phosphorus-aluminum rare earth composition, comprising the following steps:

[0108] In a reactor with water bath heating, 2.5L of water, 1394g of kaolin, and 150g of pseudo-boehmite were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol, 75.69g of cerium nitrate, 45.7g of methyl hydroxyethyl cellulose and 46.0g of ethylene glycol were added to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 150°C for 4 hours to obtain catalyst D3.

[0109] Comparative Example 4

[0110] This comparative example prepares catalytic cracking catalyst D4, wherein comparative composition 1 is used instead of boron phosphorus aluminum rare earth composition, comprising the following steps:

[0111] In a reactor with water bath heating, 3.5L water, 840g kaolin and 240g pseudo-thin were added and mixed evenly, 120g hydrochloric acid was added dropwise, stirred for 1 hour, aged at 75°C for 1 hour, and then 1125g silica sol and 450g comparative composition 1 were added, and stirring was continued to form a catalyst matrix slurry; 3.0L water was added to a pulping tank, 1080g RDSY molecular sieve was added, and after passing through a high-speed shearing machine for 20 minutes, it was added to the catalyst matrix slurry, pulped for 1 hour, and then sprayed and formed. The obtained microspheres were calcined at 500°C for 1 hour, washed with water, and dried at 130°C for 12 hours to obtain catalyst D4.

[0112] Comparative Example 5

[0113] This comparative example prepares catalytic cracking catalyst D5, wherein comparative composition 2, a rare earth compound and a dispersant are used instead of the boron phosphorus aluminum rare earth composition, comprising the following steps:

[0114] In a reactor with water bath heating, 2.5L of water, 840g of kaolin, and 150g of pseudo-boehmite were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol, 600g of comparative composition 2, 75.69g of cerium nitrate, 45.7g of methyl hydroxyethyl cellulose and 46.0g of ethylene glycol were added, and stirring was continued to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 12 hours to obtain catalyst D5.

[0115] Comparative Example 6

[0116] This comparative example prepares catalytic cracking catalyst D6, wherein comparative composition 3 is used instead of boron phosphorus aluminum rare earth composition, comprising the following steps:

[0117] In a reactor with water bath heating, 2.5L of water, 870g of kaolin, and 150g of pseudo-boehmite were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol and 600g of comparative composition 3 were added, and stirring was continued to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 120°C for 10 hours to obtain catalyst D6.

[0118] Comparative Example 7

[0119] This comparative example prepares catalytic cracking catalyst D7, wherein comparative composition 4 is used instead of boron phosphorus aluminum rare earth composition, comprising the following steps:

[0120] In a reactor with water bath heating, 2.5L of water, 870g of kaolin, and 150g of pseudo-boehmite were added, and then 90g of hydrochloric acid was slowly added and mixed evenly. After stirring for 1 hour, the mixture was aged at 75°C for 1 hour, and then 1666g of aluminum sol and 600g of comparative composition 4 were added, and stirring was continued to form a catalyst matrix slurry; 2L of water was added to a pulping tank, and 1080g of RDSY molecular sieve was added. After passing through a high-speed shearing machine for 20 minutes, the mixture was added to the catalyst matrix slurry. After pulping for 1 hour, the resulting microspheres were spray-formed and calcined at 500°C for 1 hour, washed with water, and dried at 100°C for 24 hours to obtain catalyst D7.

[0121] Comparative Example 8

[0122] This comparative example prepares catalytic cracking catalyst D8, wherein boric acid and phosphoric acid (the content of both accounts for 3% of the catalyst dry basis) are used instead of the boron-phosphorus-aluminum rare earth composition, comprising the following steps:

[0123] In a reactor with water bath heating, add 2.5L water, 1380g kaolin, 150g pseudo-boehmite, then slowly add 90g hydrochloric acid, 422g boric acid and mix evenly, stir for 1 hour, age at 75°C for 1h, add 75.69g cerium nitrate, 45.7g methyl hydroxyethyl cellulose and 46.0g ethylene glycol, stir for 1h, then add 1666g aluminum sol, 35.8g 85wt% l phosphoric acid, continue stirring to form a catalyst matrix slurry; add 2L water to a pulping tank, add 1080g RDSY molecular sieve, pass through a high-speed shearing machine for 20min, add to the catalyst matrix slurry, pulp for 1h, and then spray mold, calcine the obtained microspheres at 500°C for 1 hour, wash with water, and dry at 100°C for 24h to obtain catalyst D8.

[0124] The compositions of the raw materials corresponding to the components of the above catalysts S1-S6 and D1-D8 are shown in Table 3 below, the activity data are shown in Table 4 below, and the ACE evaluation results of the contaminated samples (contaminated with 12000 ppm nickel) are shown in Table 5.

[0125] As can be seen from Table 4, the catalysts S1-S6 of the embodiment still have relatively high activity after 800℃×17h water vapor aging, and the activities of D2, D4, D6, and D8 are significantly reduced, indicating that the addition method of boron (B) has an effect on the structure of the molecular sieve. The presence of AlPO4 in the boron-phosphorus-aluminum composition of the present invention can effectively inhibit the dealumination of the molecular sieve, offset the toxic effect of the addition of B on the catalyst, and at the same time, in the preparation process of the boron-phosphorus-aluminum rare earth composition, a mesoporous structure is formed by roasting, and boron is fixed in the pores of the composition. It is not easy to migrate to the surface of the molecular sieve during the preparation process of the catalyst, destroying the skeleton structure of the molecular sieve, so that the catalysts S1-S6 can still maintain relatively high activity stability after 800℃×17h water vapor aging. D2 uses boric acid instead of the boron-phosphorus-aluminum rare earth composition, D4 uses the uncalcined comparative composition 1 instead of the boron-phosphorus-aluminum rare earth composition, D6 uses the phosphorus-free comparative composition 3 instead of the boron-phosphorus-aluminum rare earth composition, and D8 uses boric acid and phosphoric acid instead of the boron-phosphorus-aluminum composition, and the activity is significantly reduced.

[0126] As can be seen from Table 5, after the catalysts S1-S6 were contaminated with 10000ppm nickel and 5000ppm vanadium, relative to the catalysts D1 and D3 of the comparative examples, the catalyst samples of the embodiments had high conversion rates and relatively low H2 / CH4 ratios, indicating that the addition of the composition in the embodiments helped to resist metallic nickel; relative to catalyst D2, the conversion rate of the catalyst samples of the embodiments was relatively high, and the H2 / CH4 ratio was relatively low, indicating that the addition of boron to the composition in the manner of the embodiments had better nickel resistance; relative to catalyst D5, the conversion rate of the embodiments was relatively high, indicating that the addition of rare earth in the manner of the embodiments had better vanadium resistance; relative to catalyst D4, the conversion rate of the catalyst samples of the embodiments was relatively high, indicating that the calcined composition had better metal resistance; relative to D6, D7, and D8, Examples S1 to S6 had relatively high conversion rates, indicating that the addition of the phosphorus-boron-aluminum rare earth composition in the manner of the embodiments simultaneously had both vanadium and nickel resistance effects.

[0127] Table 3 Composition of raw materials corresponding to each component in the catalyst obtained in the examples and comparative examples (on a dry basis of oxides)

[0128]

[0129] Table 4 Catalyst activity (MAT, 800℃×17h)

[0130]

[0131] Table 5 ACE evaluation results of various catalyst contaminated samples

[0132]

[0133] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A method for preparing a catalytic cracking catalyst resistant to nickel and vanadium pollution, wherein: The preparation method comprises the following steps: The first raw material is mixed with water, slurried, and then spray-formed, roasted, washed, and dried to obtain the catalytic cracking catalyst; the first raw material includes a boron-phosphorus-aluminum rare earth composition, a molecular sieve, clay, and a binder; The boron-phosphorus-aluminum-rare earth composite is a mixture of AlPO4 and B, P, Al and rare earth, and is calcined during the preparation process.

2. The preparation method according to claim 1, wherein The first raw material further includes pseudo-boehmite.

3. The preparation method according to claim 1, wherein The boron-phosphorus-aluminum-rare-earth composite is prepared by reacting an aluminum compound, phosphoric acid, a boron compound, a rare-earth compound and a dispersant and calcining at 400-700° C. The boron compound is added according to the boron content of the total mass of the boron-phosphorus-aluminum rare earth composition being 2wt% to 6wt%; The aluminum compound and phosphoric acid are added in a molar ratio of Al:P of (0.5-2.0):1; The rare earth compound is added according to the rare earth element content of the total mass of the boron-phosphorus-aluminum rare earth composition of 1.5wt% to 25wt%; The dispersant is added at 3wt% to 15wt% of the total mass of the boron-phosphorus-aluminum rare earth composition.

4. The preparation method according to claim 3, wherein The boron-phosphorus-aluminum rare earth composition is prepared by the following method 1 or method 2: Method 1: Add an aluminum compound to water, then drop phosphoric acid; then add a boron compound, a rare earth compound and a dispersant, and stir to obtain a sol containing boron, phosphorus, aluminum and rare earth; Drying the sol containing boron, phosphorus, aluminum and rare earth, and calcining at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum-rare earth composite; Method 2: Mix and disperse the aluminum compound in water, then drop phosphoric acid, add a rare earth compound and a dispersant to obtain a sol containing phosphorus, aluminum and rare earth; dry the sol containing phosphorus, aluminum and rare earth to obtain an intermediate product; The boron compound is dissolved in water, loaded in the intermediate product by an impregnation method, dried, and calcined at 400-700° C. for 1 h-4 h to obtain the boron-phosphorus-aluminum rare earth composite.

5. The preparation method according to claim 3 or 4, wherein The aluminum compound is selected from one or a combination of two or more of aluminum oxide, pseudo-boehmite, aluminum nitrate, and aluminum chloride.

6. The preparation method according to claim 3 or 4, wherein: The boron compound is selected from one or a combination of two or more of boron phosphate, boric acid, boric anhydride, ammonium borate, and ammonium fluoroborate.

7. The preparation method according to claim 3 or 4, wherein: The rare earth compound is nitrate, chloride, oxide or carbonate of lanthanum or cerium.

8. The preparation method according to claim 3 or 4, wherein: The dispersant is one or a combination of two or more of citric acid, tartaric acid, C2-8 alcohol, polyethylene glycol, cellulose derivatives, polyacrylamide and its derivatives, and guar gum.

9. The preparation method according to any one of claims 1 to 4, wherein: The specific preparation process of the catalytic cracking catalyst includes: Adding the second raw material into water and mixing evenly, adding a binder after aging to form a catalyst matrix slurry; the second raw material includes the boron phosphate aluminum rare earth composition and clay, or the second raw material includes the boron phosphate aluminum rare earth composition, clay and pseudo-boehmite; The molecular sieve is added into water, sheared, and then added into the catalyst matrix slurry, slurried, spray-formed, calcined, washed, and dried to obtain the catalytic cracking catalyst.

10. The preparation method according to claim 1, wherein: The calcination temperature of the catalytic cracking catalyst is 400-800° C., and the calcination time is 0.5-3 hours.

11. The preparation method according to claim 2, wherein: The corresponding raw materials of each component in the obtained catalytic cracking catalyst are calculated on a dry basis as follows: the content of the molecular sieve is 36wt% to 50wt%, the content of the boron-phosphorus-aluminum rare earth composition is 5wt% to 25wt%, the content of the clay is 21wt% to 43wt%, the content of the pseudo-boehmite is 0 to 13wt%, and the content of the binder is 8wt% to 15wt%.

12. The preparation method according to claim 1, wherein: The molecular sieve is selected from one or a combination of two or more of RDSY molecular sieve, REY molecular sieve, β molecular sieve and ZSM-5 molecular sieve.

13. The preparation method according to claim 1, wherein: The clay is selected from one or a combination of two or more of kaolin, elosite, montmorillonite and attapulgite.

14. The preparation method according to claim 1, wherein: The binder is selected from one or a combination of two or more of aluminum sol, silica sol or colloidal aluminum oxide or silicon oxide materials.

15. A catalytic cracking catalyst resistant to nickel and vanadium pollution prepared by the preparation method according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • Solvent-free organosiloxane composition and its use

    CA2107715A1

  • Novel anti-heavy metal cracking catalyst and preparation method thereof

    CN105728030A

  • Catalytic cracking catalyst and preparation method thereof

    CN108097287A

  • Hydrorefining and / or hydroconversion catalyst comprising an active phase in the form of a solid solution sulfide of molybdenum and tungsten

    EP1516667A1